Physical, Mechanical, and Thermal Properties of Wood Flour Reinforced Maleic Anhydride Grafted Unsaturated Polyester (UP) Biocomposites - Md. Rezaur, Rahman; Sinin, Hamdan; Mahbub, Hasan; Ruby, Baini; Abu A., Salleh (BioResources, 2015)
Physical, Mechanical, and Thermal Properties of Wood Flour Reinforced ungrafted and laleic anhydride grafted unsaturated polyester biocomposites were investigated. Composites were prepared using a Resin Transfr Moulding technique by varying wood flour loading ( 10, 15, 20, and 25 wt%) for both ungrafted and maleic anhydride grafted unsaturated polyester. Fourier transform infrared (FTIR) spectroscopic and scanning electron microscopic (SEM) analysis was utilized to study physical properties.